Imunoexpressão de rank, rankl e opg em cisto dentígero, ceratocisto odontogênico e ameloblastoma: uma revisão sistemática e meta-análise - Lima, Igor Felipe Pereira (2018)
The cysts and odontogenic tumors are one of the most important groups of injuries of the buccomaxillofacial complex. One of the most pertinent biological events in the pathogenesis of these injuries is the activation of osteoclast cells. This activation results in bone resorption. The purpose of this scientific article was to evaluate and compare RANK, RANKL and OPG immunoexpression in the dentigerous cyst, odontogenic keratocyst and ameloblastoma. This article was drafted according to the PRISMA's recommendations and Cochrane's guidelines. A record in the PROSPERO electronic base was carried out. The bibliographic sources of this article were found in PubMed, Web of Science, SciELO, LIVIVO and LILACS. To avoid the select bias, The OpenThesis and OpenGray bases were used to capture the "gray literature". The risk of bias was evaluated by the tool "JBI Critical Appraisal Checklist for Analytical Cross Sectional Studies". The meta-analysis using models random effects models was made to estimate grouped values in relation between OPG e RANKL reported by individual studies and 95% confidence intervals. The heterogeneity amont the studies was evaluated through the I² statistic. 134 studies were located, but only 8 articles met the inclusion criteria. The meta-analysis showed that the relation OPG>RANKL was higher in odontogenic keratocyst (ES = 34,0%; IC 95% = 18,0-53,0) and dentigerous cyst (ES = 38,0%; IC 95% = 16,0-62,0). In contrast, the relation OPG<RANKL was higher for the ameloblastoma (ES = 60,0%; IC 95% = 44,0-75,0). In comparison with the region of the odontogenic epithelium (ES = 47,0%; IC 95% = 29,0-65,0), the OPG<RANKL was higher in the stromal region (ES = 73,0%; IC 95% = 55,0-88,0). The results that explain the aggressive potential of ameloblastoma were found from the relation OPG<RANKL being greater in this tumor while it was lower for the odontogenic keratocyst and dentigerous cyst. It reinforces the OMS classification about odontogenic keratocyst like odontogenic cyst.